Self-Control and Cyberbullying Behavior Dynamics Among University Students: A Correlational Study within Aceh’s Academic Context - Putri Puspita Sari; Muhammad Buchori Ibrahim; Muhamad Antos Riady; Mirza Mirza (Global Education Journal, 2026)
Cyberbullying has increasingly emerged as a significant psychological issue among university students, particularly as digital communication becomes deeply embedded in higher education settings. While self-control is commonly conceptualized as a protective mechanism against aggressive conduct, empirical findings have produced mixed evidence regarding its effectiveness in predicting cyberbullying involvement among emerging adults. The present study sought to investigate the association between self-control and cyberbullying behavior among university students in Aceh. A quantitative approach with a correlational framework was applied, involving 136 active students aged 17–25 years who were recruited using a convenience sampling technique. Data were gathered through Indonesian-adapted forms of the Self-Control Scale and the Cyberbullying Scale. Prior to hypothesis testing, assumptions of normality and linearity were examined, after which Pearson’s Product Moment correlation analysis was performed. The findings revealed no statistically significant association between self-control and cyberbullying behavior (r = −0.107; p = 0.214; p > 0.05). The majority of participants exhibited moderate levels of self-control and minimal engagement in cyberbullying activities. These results suggest that self-control may not serve as a direct determinant of cyberbullying among university students in Aceh. Instead, cyberbullying behavior during emerging adulthood may be more strongly shaped by external psychosocial influences, including peer norms, situational dynamics, and culturally embedded values that operate within digital interaction contexts.